REMOVAL OF FACIAL MELANOSARCOMA OF A WHITE TIGRESS (PANTHERA TIGRIS) - A CASE REPORT - Indramani Nath; Biswadeep Jena; Sidhartha Sankar Behera; Mandakini Sahoo; Dipna Johnson (Exploratory Animal and Medical Research, 2016)
An 18 years old white tigress “Kunti” developed a large ulcerated mass originating beneath the left lower eyelid along with clinical signs of lacrimation, irritation and thwarted vision. Surgical excision was performed under tranquilization to restore normalcy. Histopathological examination revealed presence of spindle shaped anaplastic cells containing abundant melanin pigments; which was suggestive of melanosarcoma. Obligation of proper surgical techniques and maintenance of adequate postoperative measures rewarded with uneventful recovery